A computational study of a passive flow device in a mechanical heart valve for the anatomic aorta and the axisymmetric aorta - Zakaria, Mohamad Shukri; Abd. Latif, Mohd Juzaila; Mohd Salleh, Nursyaira; Basri, Adi Azriff (Penerbit Akademia Baru, 2021)
Artificial heart valves for replacing diseased indigenous heart valves were widely used. The treatment of certain types of heart disease requires mechanical valves to be implanted operatively. Healthy cardiac valves are essential to proper cardiac function. The current study presents an investigation of the pulsatile blood flow through a bileaflet mechanical heart valve (BMHV) with a vortex generator (VG) in fully open position. A St. Jude Medical Regent valve with a diameter of 23 mm was used to mount triangular VGs as a means of improving pressure gradients and reducing turbulence. The anatomic aorta and axisymmetric aorta was computed by large eddy simulation (LES) approached. The implications for both models with VGs were observed in terms of velocity magnitude, vortices and wall shear stress. The results suggested that the anatomic aorta is prone to develop more blood clotting at the leading edge of the leaflets with 2.03 m/s. Furthermore, the anatomic aorta produces higher wall shear stress with 69Pa, which possibly contributes to a high risk of thrombosis.